1998
DOI: 10.1046/j.1432-1327.1998.2530107.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol, but not its esters, triggers programmed cell death in human erythroleukemia K562 cells

Abstract: Cholesterol, its biosynthetic precursors and the cholesterol-lowering drug compactin were able to inhibit the growth of human erythroleukemia K562 cells. Compactin, farnesyldiphosphate and cholesterol were cytotoxic by the induction of apoptosis (programmed cell death, PCD). Compactin doubled the number of apoptotic cells compared to control numbers, whereas farnesyldiphosphate and cholesterol led to a fivefold increase in PCD over the control levels. At variance with cholesterol, cholesterol esters did not af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
36
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 0 publications
6
36
0
Order By: Relevance
“…The TUNEL-stained cells did not stain with antisera that recognizes either macrophage or smooth muscle cell antigens (not shown). However, we presume that the TUNEL-stained cells were macrophages because these cells were markedly reduced in the ACAT1 -/-recipients and ACAT1 deficiency causes macrophage death in vitro (36)(37)(38).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The TUNEL-stained cells did not stain with antisera that recognizes either macrophage or smooth muscle cell antigens (not shown). However, we presume that the TUNEL-stained cells were macrophages because these cells were markedly reduced in the ACAT1 -/-recipients and ACAT1 deficiency causes macrophage death in vitro (36)(37)(38).…”
Section: Resultsmentioning
confidence: 96%
“…Because in vitro studies have demonstrated that cholesterol toxicity associated with ACAT inhibition can cause cell death in macrophages (36)(37)(38), we examined the extent of apoptosis and necrosis in arterial lesions by TUNEL staining of aortic cross sections from study animals. The proportion of TUNEL-stained cells was threefold higher in ACAT1 -/-recipient mice than in controls (18% vs. 52%, P = 0.037), indicating that necrotic and apoptotic cell death contributed to the diminished numbers of macrophages in lesions ( Figure 3, c and d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 In contrast, inhibition of cholesterol biosynthesis by squalene epoxidase inhibitors TU-2078 and NB-598 prevents apoptosis in L6 myoblasts 30 and cholesterol itself induces apoptosis in human erythroleukemia K562 cells. 31 Taken together, the relationship between the inhibition of cholesterol end products and cell death appears to be dependent on the intracellular cholesterol content rather than other end products in the mevalonate pathway, as shown in a study using a neuronal cell system and a HMG-CoA reductase inhibitor. 32 In the present study, four metabolites of cholesterol synthesis, cholesterol, squalene, lanosterol and desmosterol, were supplemented in cell cultures treated with lovastatin.…”
Section: Figurementioning
confidence: 93%
“…Cholesterol also serves as a regulator of gene transcription, protein degradation, and enzyme activity and has been implicated in programmed cell death (1,2). Moreover, the role of cholesterol in signal transduction is being increasingly recognized (3).…”
mentioning
confidence: 99%